Effectiveness of pharmacovigilance: Multifaceted educational intervention related to the knowledge, skills and attitudes of multidisciplinary hospital staff - Varallo, Fabiana Rossi [UNESP]; Planeta, Cleopatra S. [UNESP]; Mastroianni, Patricia de Carvalho [UNESP] (Elsevier, 2017)
OBJECTIVES: Most educational interventions in pharmacovigilance are designed to encourage physicians to report adverse drug reactions. However, multidisciplinary teams may play an important role in reporting drugrelated problems. This study assessed the impact of a multifaceted educational intervention in pharmacovigilance on the knowledge, skills and attitudes of hospital professionals. METHOD: This prospective, open-label, non-randomized study was performed in a medium-complexity hospital in São Paulo, Brazil. The intervention involved four activities: 1) an interactive lecture, 2) a practical class, 3) a pre-post questionnaire administered to professionals on a multidisciplinary team, and 4) educational material. The intervention’s impact on the professionals’ knowledge and skills was assessed using the World Health Organization’s definitions. The intervention’s effect on the professionals’ attitudes was analysed by the prevalence of adverse drug event reports (adverse drug reactions, medication errors, therapeutic failure and drug quality deviations) and the relevance (seriousness and expectancy) of the events. RESULTS: One hundred seventy-three professionals were enrolled. A 70-fold increase in the number of adverse drug event reports was observed during the 12 months post-intervention. The intervention improved the professionals’ form-completion skills (p<0.0001) and their knowledge of pharmacovigilance (p<0.0001). The intervention also contributed to detecting serious drug-induced events. The nursing staff reported medication errors, and pharmacists and physiotherapists recognized serious adverse drug reactions. Physicians communicated suspicions of therapeutic failure. CONCLUSIONS: A multidisciplinary approach to drug-safety assessments contributes to identifying new, relevant drug-related problems and improving the rate of adverse drug event reporting. This strategy may therefore be applied to improve risk communication in hospitals.
Keywords: Attitudes; Health knowledge; Interventional studies; Pharmacovigilance; Practices; Product surveillance